2020
DOI: 10.3934/publichealth.2020044
|View full text |Cite
|
Sign up to set email alerts
|

Corona pandemic: awareness of health care providers in Pakistan

Abstract: Introduction Corona pandemic has resulted in a high mortality rate among health care professionals. The purpose of this study was to assess the knowledge and practices of health care providers during this pandemic in Punjab, Pakistan. Methods A web based cross sectional survey was conducted during 2 nd of April to 20 th April 2020 targeting health care professionals working in Punjab, Pakistan. A sample of 540 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
7
2
Order By: Relevance
“…Not surprisingly, most of the participants in the study were housewives. This result is in contrast with the results of a study carried out in Pakistan in which it was shown that men had a better attitude towards the prevention of infection than women [ 30 ]. The current study showed that mass media (e.g., radio, TV, etc.)…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Not surprisingly, most of the participants in the study were housewives. This result is in contrast with the results of a study carried out in Pakistan in which it was shown that men had a better attitude towards the prevention of infection than women [ 30 ]. The current study showed that mass media (e.g., radio, TV, etc.)…”
Section: Discussioncontrasting
confidence: 99%
“…still have a greater and essential impact on people’s awareness and attitude than virtual networking applications [ 32 ]. This finding contrasts with the findings of a study in Pakistan in which most participants would get their information from social media [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations